Effects of Hedysarum coronarium L. (sulla) as a Green Manure along with Nitrogen Fertilizer on Maize Production - Mohammad Mahdi Akbarian; Tahereh Mojaradi; Fatemeh Shirzadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Green manure as a source of soil organic matter is an important indicator of potential agricultural ecosystems capable of preventing erosion, reducing runoff, increasing soil permeability, improving ventilation, ameliorating the temperature, and enhancing the function of microorganisms. Therefore, to investigate the effects of green manure Sulla (Hedysarum coronarium) and nitrogen fertilizer on maize yield in Kermanshah, an experiment was carried out as split-plot in a randomized complete block design with 3 replications. The main factor was the use of Sula in two levels, namely application and non-application, while, the sub-factor was the application of N fertilizer at four levels of zero, 200, 400 and 500 kg/ha. The highest leaf area index was observed by 400 kg/ha N application along with green manure. Grains per ear determined using green manure and nitrogen fertilizer at levels of 0, 200, 400 and 500 kg/ha increased by 8, 10, 15, and 15%, respectively. The result showed that the Sulla green manure treatment increased the grain yield by 10% compared to the control treatment. Furthermore, the highest grain yield was obtained under two treatments of 400 and 500 kg N/ha which was significantly different from other levels of N applications. The application of green manure application also increased the maize protein content by 8% with a rise in the highest levels of nitrogen fertilizer. Meanwhile, the application of Sulla as a green fertilizer or pre-planting had a positive impact on increasing soil organic matter and maize yield. Therefore, cultivation of Sulla can be considered a positive task towards sustainable agriculture.